Přesný diferenční teploměr - Sieklik, Ivan (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2015)
Práca sa zaoberá princípom a realizáciou merania štruktúrneho parametru indexu lomu, pomocou diferenciálneho teplomera. V tejto práci sú uvedené základné vlastnosti atmosférického prenosového prostredia a ich vplyv na šíriacu sa optickú vlnu. Ďalej sú predstavené a opísané základné typy senzorov určené na meranie teploty. Hlavným cieľom práce je navrhnúť diferenciálny teplomer s možnosťou merania štruktúrneho parametru indexu lomu.

This work describes the principles of measurements of refractive-index structural parameter. This parameter represent intensity of atmospheric turbulence which is measured by a differential temperature meter. Basic properties of atmospheric transmission environment are specified and their influence on optical wave is stated. Furthermore, this thesis also describes fundamental types of sensors dedicated to temperature measurements. The aim of this work was to create a differential temperature meter which is able to measure the refractive-index structural parameter.
High precision differential thermometer
Keywords: Atmosféra; teplota; meranie; atmosférické turbulencie; vlna; index lomu; Atmosphere; temperature; measurement; atmospheric turbulence; wave; refractive index